The Role of Bdnf in 17β-Estradiol-Induced Facilitation of Extinction of Cocaine Seeking - (:unkn) unknown (My University, 2016)
Females are more susceptible to drug dependence than males, and these differences in addictive behaviors are mediated, in large part, by 17β-estradiol (E2). E2 enhances memory in a variety of behavioral paradigms and may act to enhance the formation of drug-related memories. Interestingly, due to its mnemonic effects, E2 promotes drug seeking, but also may aid in extinguishing drug seeking behaviors. Treatment of addiction is modeled through extinction, and the infralimbic medial prefrontal cortex (IL-mPFC) is responsible for inhibiting drug seeking after extinction. However, the cellular mechanisms by which E2 facilitates extinction remain unknown. Previous work suggests that the memory-enhancing effects of E2 are mediated by brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin-related kinase B (TrkB). Thus, we hypothesized that E2-facilitated extinction is dependent upon BDNF/TrkB signaling. To identify this mechanism, we used the conditioned place preference paradigm (CPP) in which rats are trained to associate one chamber, but not another, with cocaine. Following conditioning, ovariectomized rats were systemically administered E2 prior to each extinction trial. Furthermore, IL-mPFC infusions of a Trk receptor antagonist did not impair, but facilitated extinction. Systemic injections of a TrkB receptor antagonist and E2 did impair extinction, whereas injections of vehicle and E2 facilitated extinction. The results of this experiment are in agreement with our hypothesis, however, an E2-facilitated extinction was not consistently observed in this study. In order to determine the cellular mechanism by which E2 increases intrinsic excitability in IL-mPFC pyramidal neurons, we performed patch-clamp electrophysiology while bath-applying Trk receptor antagonists. Our results revealed that blockade of Trk receptors attenuated E2-induced increase in intrinsic excitability. These results indicate that E2 potentiates intrinsic excitability via BDNF/TrkB signaling in IL-mPFC pyramidal neurons. This study demonstrates that optimizing E2 levels and/or augmenting BDNF function could enhance therapeutic interventions in alleviating learning and memory disorders such as drug addiction.
Keywords: Addiction; Brain-Derived Neurotrophic Factor; Cocaine; Estradiol; Excitability; Extinction